On individuality and social forms : selected writings - Simmel, Georg, 1858-1918.; University of Chicago. Press (Chicago: University of Chicago Press, 1971)
Half of the material included in this edition of Simmel's writings represents new translations. This includes Simmel's important, lengthy, and previously untranslated "Group Expansion and the Development of Individuality," as well as three selections from his most neglected work, 'Philosophy of Money';in addition, the introduction to 'Probleme der Geschichtsphilosophie', chapter one of the 'Lebensanschauung', and three essays are translated for the first time.
I: Philosophy of the social sciences -- How is history possible? -- How is society possible? -- The problem of sociology -- The categories of human experience -- II: Forms of social interaction -- Exchange -- Conflict -- Domination -- Prostitution -- Sociability -- III: Social types -- The stranger -- The poor -- The miser and the spendthrift -- The adventurer -- The nobility -- IV: Forms of individuality -- Freedom and the individual -- Subjective culture -- Eros, platonic and modern -- V: Individuality and social structure -- Group expansion and the development of individuality -- Fashion -- The metropolis and mental life -- Subordination and personal fulfillment -- VI: Forms versus life process: the dialectics of change -- Social forms and inner needs -- The transcendent character of life -- The conflict in modern culture.
Bibliography: page 395.
Keywords: Sociology; Social psychology